2018
DOI: 10.1186/s12864-018-5193-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival marker genes of colorectal cancer derived from consistent transcriptomic profiling

Abstract: BackgroundIdentification of biomarkers associated with the prognosis of different cancer subtypes is critical to achieve better therapeutic assistance. In colorectal cancer (CRC) the discovery of stable and consistent survival markers remains a challenge due to the high heterogeneity of this class of tumors. In this work, we identified a new set of gene markers for CRC associated to prognosis and risk using a large unified cohort of patients with transcriptomic profiles and survival information.ResultsWe built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…A recent study has exhibited that patients with NPR3-positive tumors can show remarkably declined progression-free and overall survival [30]. Jorge Martinez-Romero et al have also indicated that NPR3 is upregulated in colorectal cancer samples and considered as a marker of poor outcome [31]. The targeting relationship between miR-140-5p and NPR3 was veri ed in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…A recent study has exhibited that patients with NPR3-positive tumors can show remarkably declined progression-free and overall survival [30]. Jorge Martinez-Romero et al have also indicated that NPR3 is upregulated in colorectal cancer samples and considered as a marker of poor outcome [31]. The targeting relationship between miR-140-5p and NPR3 was veri ed in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…To explore the occurrence and development of diseases from a novel perspective, bioinformatics analysis is becoming an emerging and effective technique [47,48]. Clear cell renal cell carcinoma is a major histological subtype of renal cell carci-noma, which is one of the deadliest forms of urinary malignancy [1].…”
Section: Discussionmentioning
confidence: 99%
“…MSLN had been accepted to be a candidate biomarker in colon cancer [37]. Qian Z et al demonstrated that INHBB predicted worse survival rates in patients with colorectal cancer [38] DCBLD2 was also identified as one of survival markers genes in colon cancer through consistent transcriptomic profiling by Martinez-Romero J et al [26]. Gylfe AE et al performed exome sequencing on a total of 25 colorectal cancer and corresponding healthy colon tissues, demonstrating that MAP1B was one of the candidate oncogene in patients with colon cancer [39].…”
Section: Discussionmentioning
confidence: 99%
“…C-index, also known as concordance" statistic or C-statistic, is a measure of goodness of fit for survival outcomes in a CPH model, and higher C-index means higher predictive ability [21]. Therefore, to further confirm the performance of our multigene panel, we compared the C-indexes, calculated by using the R package "survcomp [22]" , with a total of 10 biomarkers reported by others [23][24][25][26][27][28][29][30][31][32][33]. Student T test was used to compare C-indexes between two groups.…”
Section: Comparison Of the Prognostication Performance Of Our Multigementioning
confidence: 99%
See 1 more Smart Citation